2012
DOI: 10.1097/01.ogx.0000422962.85249.f8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Is the Leading Cause of Death Among Endometrial Cancer Patients

Abstract: Most women with endometrial cancer survive the disease. The 5-year survival among patients diagnosed and treated at early stages is estimated to be 96%. A large number of studies have demonstrated a high prevalence of cardiovascular death among endometrial cancer survivors. It is possible that obesity and metabolic syndrome, risk factors for cardiovascular disease, may contribute to the high prevalence of cardiovascular death among endometrial cancer survivors. No prior studies have examined causes of death am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 0 publications
4
55
0
2
Order By: Relevance
“…Multiple studies have found that women with early-stage endometrial cancer are at higher risk of mortality from competing noncancer causes than from their primary cancer (2)(3)(4)(5). This is due to the favorable prognosis associated with surgical treatment (2,4,6) and the high prevalence of risk factors for cardiovascular disease (7,8) and second malignancies (9).…”
Section: Introductionmentioning
confidence: 96%
“…Multiple studies have found that women with early-stage endometrial cancer are at higher risk of mortality from competing noncancer causes than from their primary cancer (2)(3)(4)(5). This is due to the favorable prognosis associated with surgical treatment (2,4,6) and the high prevalence of risk factors for cardiovascular disease (7,8) and second malignancies (9).…”
Section: Introductionmentioning
confidence: 96%
“…Improving body weight in EC and BC survivors may decrease morbidity and have the potential to improve overall survival since relative risk of death for obese EC women with a body mass index (BMI) 30-34 was 2.53, and BMI N40 was 6.25; the highest of all cancers [12,13]. Specifically, the risk of death from cardiovascular disease (CVD) related causes begin to exceed the risk from cancerrelated causes 3.5 years after EC diagnosis [14]. Thus, interventions that address dietary change and increased exercise together are necessary to elicit weight-loss and improve cardiovascular disease risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the risk of death from CVD-related causes in gynecological cancer begins to exceed the risk from cancer-related causes 3.5 years after diagnosis (Figure 5.1) [31]. In a prospective study by Ward et al, researchers examined the relationship between cancer, BMI, and risk of death, demonstrating a significantly increased risk of death in obese women with endometrial cancer.…”
Section: Female Cancer Survivorshipmentioning
confidence: 98%